THE BARCELONA WAY : How to Create a High-Performance Culture - Hughes, Damian, Prof. (London : Pan Books, 2019)
Lessons from the most successful football club on the planet about how to build a winning culture in any working environment
Includes bibliographical pages : 303-311
Keywords: Futbol Club Barcelona; Success in business; Organizational behavior; Corporate culture